THE EFFECTS of HEAVY MENSTRUAL BLEEDING on SCHOOL and SOCIAL LIFE in NURSING and MIDWIFERY STUDENTS - KOÇOĞLU, Ferdane; KOCAÖZ, Semra; KARA, Pınar (Göbeklitepe Medical Science Journal, 2022)
Purpose: This study was conducted with the aim of determining the frequency of heavy menstrual bleeding (HMB) in nursing and midwifery students and the effect of this health problem on their school and social life. Materials and Methods: This sectional study was conducted with 416 female students studying at the nursing and midwifery section of the health-related university higher education institution. The data were collected with a questionnaire including 30 questions on the sociodemographic and menstrual features and the effects of HMB on school and social life. Descriptive statistics were used to evaluate the data while paired comparisons were performed with the chi-square test. Results: The prevalence of HMB determined according to the criteria was found to be 40.6% There was a statistically significant relationship between the presence of HMB in the students and the level of the effect of menstrual bleeding on the physical activity, sleep, productivity at home, and the school, social, family and getting dressed living areas (p<0.05). Those with HMB were found to experience more shortness of breath and sleeplessness, to limit their social activities, and to have difficulties concentrating and understanding the lectures compared to those without HMB; the school success, attendance, social relationships, daily activities, self-confidence, and choosing and using clothing were found to be affected in addition to avoidance of visiting places where a long stay during the day was likely (p<0.05). Conclusion: We found that HMB was common in nursing and midwifery students and that it had a negative effect on the school and social areas along with many areas of their life. The students need to be made more aware of the diagnosis and treatment of HMB and guided so that they show health-seeking behavior in order to decrease the problems experienced in the school and social life areas.